Necrotizing Enterocolitis in an Asphyxiated Premature Infant - Sunarka Sunarka; Hamid S.; Sudaryat S. (Paediatrica Indonesiana, 1996)
A case of NEC in a six days old asphyxiated premature infant was reported. The diagnosis was based on predisposing factors including low weight infant, severe ash- pyxia, her mother sufferef from fever and premature rupture of the amniotic membrans more than 24 hours. Clinical features include abdominal distention with discoloration of the abdominal wall, vomiting bloody stool, sclerema, temperature instability, jaundice, and respiratory distres. Plain abdominal X ray examination showed significant intestinal distention, and hiponatremia. The patient was treated with supportive therapy and surÂgical intervention was not done because the poor condition of the patient. The prognosis of NEC depend on the severity of disease, with mortality rate varies from 0 to 64%. The prognosis of our case is not good and on January 28, 1904 she died.